Toll-like receptor upregulation in liver and peripheral blood mononuclear cells of patients with amoebic liver abscess - Sandhya Khunger; Abhishek Mewara; Upninder Kaur; Ajay Duseja; Pallab Ray; Naveen Kalra; Navneet Sharma; Rakesh Sehgal (Immunobiology)
Aim: We aimed to understand the host and microbe interactions at the time of infection and inflammatory response in amoebic liver abscess (ALA) patients based on toll-like receptor (TLR) expression (mRNA), cytokine and IgG subtypes levels. Methods and results: Liver aspirates from 100 ALA patients and 11 liver autopsy samples were used as negative controls. Blood samples from 100 ALA and 41 healthy individuals were collected. mRNA expression of TLR 1 to 9 genes was measured using reverse transcriptase polymerase chain reaction (RT-PCR). Serum cytokines level was quantified by flow cytometry. In-house ELISA for the analysis of IgG and its subtypes in the serum samples was performed. A total of 7 TLR genes (TLR1, TLR2, TLR4, TLR6, TLR7, TLR8 and TLR9) and 6 TLR genes (TLR1, TLR2, TLR3, TLR4, TLR5 and TLR8) were found to be elevated in liver aspirates and PBMCs respectively. Increased serum cytokine levels were observed in ALA patients vs. healthy controls. Interestingly, a significant increase in IgG and its subtypes (IgG1, IgG3 and IgG4) was found in the serum of ALA patients. Conclusion: Increased levels of TLR, pro- and anti-inflammatory cytokines, IgG and its subtypes, are possibly linked with early-stage infection in ALA patients. Impact statement: The role of TLRs in association with ALA might provide insights into new therapeutic strategies.